Youtube “Satu Persen” Sebagai Sarana Komunikasi Massa Pengembangan Diri Mahasiswa - Ervita Riliana; Nina Yuliana (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
YouTube, which is a means of mass communication, now has an impact on student self-development. YouTube "One Percent" is a show that contains content about self-development. Students with all the problems of self-development that are not taught at school begin to improve their habits, lifestyle, finance, socializing through the educational show "One Percent". The purpose of this study is how the form of utilization of Youtube "One Percent" as a means of self-development and to find out how the impact of the audience of the YouTube channel "One Percent" as a means of communication in developing themselves. The research approach used is a qualitative approach. The nature of exploratory qualitative research with research methods using in-depth interviews. The results in this study are the utilization of YouTube One Percent as a means of mass communication for self-development is considered effective in student self-development, and has a positive impact on students.